Nature as a symbol of Malay thinking - Sujud, Arba'ie; Azmi, Azie; Nik Muhamad Affendi, Nik Rafidah (Human Resource Management Academic Research Society, 2022)
Nature plays an important role in the storytelling of the traditional Malay society. They wisely used nature to display the elements of teaching, social protest, satire, and social wisdom to solve the difficulties at that time. Modernization has increasingly depreciated the folktales. But there are efforts made by the community to resurrect them. Therefore, this study tries to identify and analyze the elements of nature as a symbol of traditional Malay thinking. This study uses text analysis. The results showed the wisdom of the traditional Malay community to use natural resources as a medium to convey a message to the members of the community as nature has a close relationship with human life.